The contributions of the National School of Socioeducation courses for professionals who work with socio-educational measures from the point of view of moral psychology - Monteiro, Tamires Alves (2025)
The objective of this work was to analyze, from the perspective of moral psychology, some courses of the National School of Socioeducation, seeking for set a relation with the perception of former students about the contributions obtained from these courses. For this task was realized a documental and exploratory research, the latter making using the clinical interview as one of the methodological instruments. The data was analyzed in a qualitative way and categorized by the methodological process of content analysis from Laurence Bardin. The findings evidenced that the ENS’ courses brought substantial improvements to the students, however, these contributions was more in the information level than in terms of a change of stance in the direction socio-educational work.  We believe that moral psychology studies can be useful for ENS courses, bringing contributions mainly to the process of becoming aware of socio-educational practice.